Effects of Nd and Co co-doping on phase, microstructure and ferromagnetic properties of bismuth ferrite ceramics - Pornchanok Lawita (2018)
In this work, the samples of Bi 0.95 Nd 0.05 Co x Fe 1-x O 3 (BNFCO) with x=0, 0.03, 0.05 and 0.07 mol fraction, were prepared by a solid state reaction. The effect of Nd and Co co-doping concentration on phase, densification, microstructure and ferromagnetic properties were examined. The BNFCO powders were prepared using a mixed-oxide method and calcined at 800 °C for 2 h before being pressed and sintered at various temperatures in the range of 825-900 °C for 2 h. An increase in Co co-doping content increased density of the ceramics. Phase analysis by X-ray diffraction indicated the existence of rhombohedral phase for all BNFCO powders and ceramics. Microstructural investigation using the scanning electron microscope showed a reduction of grain size with increasing Co content. Magnetic hysteresis loops showed that remanent magnetization and coercive magnetic field of the Co-doped samples were improved. © 2012 Elsevier Ltd and Techna Group S.r.l.